Spatial Distribution of Heavy Metals from Anthropogenic Origin, in the Sub Basin of the Alto Balsas, Puebla, and Tlaxcala - Torres-Rosique, Jonathan; Tamaríz-Flores, José Víctor; Castro-González, Numa Pompilio; Castelán-Vega, Rosalía del Carmen; Pérez-Osorio, Gabriela (REVISTA TERRA LATINOAMERICANA, 2025)
In the metropolitan area of Puebla and Tlaxcala, waste discharge into the Alto Balsas sub basin constitutes an environmental issue that has increased throughout recent years due to the expansion of urban settlements, causing health issues derived from consumption and irrigation water use. The objective was to evaluate heavy metal contamination in soils and surface water used for agricultural production and to conduct a spatial analysis of heavy metals locating the potential sources of contamination. The study was carried out in three representative areas of the sub-basin, collecting water and soil samples. The geoaccumulation index (Igeo) and enrichment factor (EF) were obtained, and the spatial distribution analysis for heavy metals was made by interpolation using the IDW method. The results showed median concentrations of Cd, Co, Cr, and Ni above the U.S. EPA recommendations for irrigation water-use. Cr values exceed the maximum levels for agricultural soil-use. The Igeo showed strong to moderate contamination in concentrations of Cd, Co, and Zn elements, while Cr, Cu, and Ni resulted in moderate contamination. The EF showed significant enrichment for elements such as Cd, Co, Cr, Cu, and Zn, proving that the contamination is related to anthropogenic sources. From the spatial distribution, it is possible to identify the contamination sources of heavy metals, associating the causes with the increasing urban areas and the industrial growth in the Alto Balsas region, which, due to the lack of regulation for waste discharges contributes to the accumulation of heavy metals, generating pollution in agricultural soils.